Us, in progress : short stories about young Latinos - Delacre, Lulu (Harper, 2017)
Contains a collection of eleven short stories about young Latinos including a young girl spending a day at her father's burrito cart and a Texan boy overcoming the prejudice built from his father's Border Control job.